I won’t be #BulliedIntoBadScience - Logan, Corina (Septentrio Conference Series, 2018)
Watch the VIDEO. The #BulliedIntoBadScience (BIBS) campaign consists of early career researchers leading individuals and institutions in adopting open practices to improve research rigor (from all fields, not only the sciences). I will share how BIBS started and discuss what we as researchers are doing to stop exploiting ourselves and the public when sharing our research with each other and the public. We are developing best practices for facilitating higher quality research and tackling biases in this rapidly changing world of scholarly publishing. I will share case studies at the individual level (e.g., how a PI can run an open and transparent lab), at the level of the academic community (e.g., changing editorial practices via efforts such as Editors4BetterResearch and Peer Community in Ecology), and at the level of institutions (e.g., serving as Data Champions and advising governments). We at BIBS aim to be a central resource for people to share and organize best practices, thus it is useful for researchers, librarians and research administrators.